The Effect of Post-Anesthesia Team Handover on Hypoxia in Post-Anaesthesia Care Unit (PACU) - Astilia, Astilia (PT. Hafasy Dwi Nawasena, 2024)
Miscommunication in handover from the operating room to the Post-Anaesthesia Care Unit (PACU) often occurs and can cause diagnostic and therapeutic delays and trigger complications. One of the most frequent complications in the PACU room is Hypoxia.Post-Anaesthesia Team Handover (PATH) using SBAR is expected to reduce the incidence of hypoxia in the PACU, reduce handover interruptions, improve communication and information between health workers. The study aimed to determine the effects of Post Anesthesia Team Handover (PATH) on Hypoxia in Post-Anaesthesia Care Unit (PACU). This study used a pre-posttest quasi-experimental design with a control group. Purposive sampling was applied to recruit 68 respondent to participate in the study. There was a significant difference between the hypoxia before and after the use PATH with SBAR in the intervention group compared to the control group (p = 0,002). Post Anesthesia Handover Register using SBAR can improve communication during handover in the PACU to prevent hypoxia.